2016
DOI: 10.1186/s12987-016-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and in situ hybridization study of urate transporters GLUT9/URATv1, ABCG2, and URAT1 in the murine brain

Abstract: BackgroundUric acid (UA) is known to exert neuroprotective effects in the brain. However, the mechanism of UA regulation in the brain is not well characterized. In our previous study, we described that the mouse urate transporter URAT1 is localized to the cilia and apical surface of ventricular ependymal cells. To further strengthen the hypothesis that UA is transported transcellularly at the ependymal cells, we aimed to assess the distribution of other UA transporters in the murine brain.MethodsImmunostaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…Recent reports have indicated that ependymal cells, which separate the CSF from brain parenchyma, express several transporters, such as L-glutamate transporters 33) and urate transporters. 34) In addition to these reports, Yasuda et al have found that arachnoid barrier epithelial cells, which are present in meninges, express several kinds of transporters, such as P-glycoprotein and ATPbinding cassette transporter G2. 35) Thus, there is a possibility that these epithelial cells also involves in vivo spermine elimination from the CSF.…”
Section: Resultsmentioning
confidence: 96%
“…Recent reports have indicated that ependymal cells, which separate the CSF from brain parenchyma, express several transporters, such as L-glutamate transporters 33) and urate transporters. 34) In addition to these reports, Yasuda et al have found that arachnoid barrier epithelial cells, which are present in meninges, express several kinds of transporters, such as P-glycoprotein and ATPbinding cassette transporter G2. 35) Thus, there is a possibility that these epithelial cells also involves in vivo spermine elimination from the CSF.…”
Section: Resultsmentioning
confidence: 96%
“…Urate needs to pass through the BBB and/or BCSFB by specific transporters to enter the CSF and brain ISF. Among urate transporters, GLUT9/SLC2A9, urate transporter 1 (URAT1/SLC22A12), and breast cancer resistance protein (BCRP/ABCG2) were reported to play important roles in the regulation of serum uric acid [ 130 , 134 ] and are all expressed in the BBB and/or BCSFB [ 142 , 143 , 144 ].…”
Section: Urate Transporters In Choroid Plexus Epithelial Cellsmentioning
confidence: 99%
“…An immunohistochemical analysis of mouse brain frozen sections revealed the expression pattern of Glut9 in ependymal cells, tanycytes lining the floor of the ventral third ventricle, and NeuN-positive cells in the brain parenchyma, although submembrane localization (apical or basolateral) was inconclusive [ 143 ]. Furthermore, immunohistochemistry using a methacarn-fixed mouse brain revealed Glut9 expression on the luminal membrane of the brain capillary endothelium [ 143 ]. Although these approaches failed to show Glut9 expression in the CP, the presence of Slc2a9 was identified not only in ependymal cells but, also, in CP epithelial cells by highly sensitive in-situ hybridization [ 143 ].…”
Section: Urate Transporters In Choroid Plexus Epithelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations